2017
DOI: 10.1515/sjecr-2016-0080
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Risk Factors Among Women With Osteoporosis

Abstract: Osteoporosis is a progressive bone disorder that can be infl uenced by many diff erent factors. A cross-sectional study has been conducted with the aim to assess the prevalence of risk factors as well as to identify the possible causes of improvement of the disease. Th e study population consisted of 97 women older than 35 who had previously been diagnosed with osteoporosis. Dualenergy X-ray Absorptiometry (DXA) scan was used to determine bone mineral density (BMD) in order to assess the current state of the d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 18 publications
0
2
0
Order By: Relevance
“…It is important, however, that osteoporosis is often hidden in the same high prevalence, causing a large number of people to inflict high economic and social costs and spend tens billions of dollars in annual costs in a country like the United States [4]. Pelvic fractures are responsible for most of the costs and deaths caused by osteoporosis, and septum fractures also cause significant pain and disability in patients with only one-third of these fractures diagnosed clinically and these problems have a significant effect on the quality of life of individuals, especially women, is at the age of menopause [5,6].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is important, however, that osteoporosis is often hidden in the same high prevalence, causing a large number of people to inflict high economic and social costs and spend tens billions of dollars in annual costs in a country like the United States [4]. Pelvic fractures are responsible for most of the costs and deaths caused by osteoporosis, and septum fractures also cause significant pain and disability in patients with only one-third of these fractures diagnosed clinically and these problems have a significant effect on the quality of life of individuals, especially women, is at the age of menopause [5,6].…”
Section: Introductionmentioning
confidence: 99%
“…The results of existing studies confirm the high role of genetics and race in bone density and osteoporosis. Recent studies in recent years have shown that family history of osteoporosis increases the risk of osteoporosis, and it is estimated that 50-80% of the difference in bone mass between individuals is due to their genetic and hereditary differences [6,7].…”
Section: Introductionmentioning
confidence: 99%